PERANCANGAN SISTEM INFORMASI PELAYANAN e-LOKET DI PT POS BERBASIS ANDROID (Studi Kasus: Kantor Pos Banyuwangi) - Evin Lutfiyana Fitriya Ningsih; Fajriyanto Fajriyanto (Jurnal Riset Sistem Informasi, 2025)
This research aims to design and implement an Android-based e-Loket Information System at the Banyuwangi Post Office as a solution to address long queues, service delays, and the limitations of the manual system currently in use. This system is designed to streamline the service process, from queue number acquisition to service selection. The research method used is descriptive analytical, with data collection through observation and interviews. The system design was conducted using the Waterfall model, which includes the stages of request, design, implementation, verification, and maintenance. The system is equipped with automatic queue number acquisition and digital dialing. The results indicate that the implementation of the Android-based e-Loket information system can improve transaction processes and increase customer satisfaction, thus having a positive impact on the Banyuwangi Post Office environment